Traditional and new candidate cardiac biomarkers assessed before, early, and late after half marathon in trained subjects - Vassalle, C.; Masotti, S.; Lubrano, V.; Basta, G.; Prontera, C.; Di Cecco, P.; Del Turco, S.; Sabatino, L.; Pingitore, A. (European Journal of Applied Physiology, 2018)
Purpose: Cardiac Troponins (cTnI, cTnT), NT-proBNP, and galectin-3 (GAL-3) mirror cardiomyocyte injury, stretch, and fibrosis. However, although these biomarkers has been thoroughly studied in marathon or ultramarathon, the effects occurring running shorter distances, as half-marathon, are less known and data are generally limited to immediately post-race evaluation. Moreover, significant variation of alpha-1 antitrypsin (AAT), an anti-protease factor with anti-inflammatory properties, has been recently observed in heart failure, but not investigated in paraphysiological settings. The aim of the study was to evaluate these biomarkers concentration and trends in trained runners before half-marathon run and during a 48-h recovery period. Methods: In 18 half-marathon runners (15 males, 46 ± 6 years), cTnI, GAL-3 (Architect, Abbott), cTnT, NT-proBNP (Cobas e411, Roche), and AAT (Abcam, Cambridge, UK) were evaluated at rest, immediately post-run, and at 24 and 48-h recovery period. Results: cTnT, NT-proBNP, and GAL-3 transiently increased after post-race, but normalized at 24 h (GAL-3 p < 0.01, cTnT < 0.001) or 48 h (NT-proBNP < 0.001), while cTnI and AAT did not significantly change. The frequency of values exceeding the diagnostic threshold, as evaluated at baseline and after the race, did not differ for cTnI (Chi² = 1.1, p = ns), and NT-proBNP (Chi² = 6, p = ns), but significantly increased for cTnT (Chi² = 23, p < 0.001) and GAL-3 (Chi² = 6.3, p < 0.05). None of the subjects showed AAT values exceeding the reference range at baseline and at any of the time points after the race. Conclusion: The transient cTnT, NT-proBNP, and GAL-3 increase may suggest a temporary stress on the myocyte. However, being the increase of all biomarkers moderate and reversible, it may represent a physiological response to acute exercise.